2013
DOI: 10.3168/jds.2013-6917
|View full text |Cite
|
Sign up to set email alerts
|

Identification of virulence factors in 16S-23S rRNA intergenic spacer genotyped Staphylococcus aureus isolated from water buffaloes and small ruminants

Abstract: Staphylococcus aureus is an important human and animal pathogen, and is regarded as an important cause of intramammary infection (IMI) in ruminants. Staphylococcus aureus genetic variability and virulence factors have been well studied in veterinary medicine, especially in cows as support for control and management of IMI. The aim of the present study was to genotype 71 Staph. aureus isolates from the bulk tank and foremilk of water buffaloes (n=40) and from udder tissue (n=7) and foremilk (n=24) from small ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…And more, according to previous studies [ 11 , 13 , 15 ], except for Brazil, Germany and USA, the remaining countries showed isolates encoding at least 2 virulence factors out of staphylococcal complement inhibitor ( scn ), chemotaxis inhibitory protein of S. aureus ( chp ) and staphylokinase ( sak ). These virulence factors show activity prevalently against the human innate immune system but their presence among isolates recovered in herds with high prevalence of S. aureus mastitis suggests their involvement also in bovine mammary gland immune response [ 16 ], and should be further studied, especially in Colombia and Tunisia where this gene cluster is quite common [ 17 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…And more, according to previous studies [ 11 , 13 , 15 ], except for Brazil, Germany and USA, the remaining countries showed isolates encoding at least 2 virulence factors out of staphylococcal complement inhibitor ( scn ), chemotaxis inhibitory protein of S. aureus ( chp ) and staphylokinase ( sak ). These virulence factors show activity prevalently against the human innate immune system but their presence among isolates recovered in herds with high prevalence of S. aureus mastitis suggests their involvement also in bovine mammary gland immune response [ 16 ], and should be further studied, especially in Colombia and Tunisia where this gene cluster is quite common [ 17 ].…”
Section: Discussionmentioning
confidence: 94%
“…As previously described [ 15 ], S. aureus isolates harbouring genes coding for clumping factor ( clfA ), a cell wall-associated protein ( fmtB ), and collagen-binding protein ( cna ) have a greater capability to adhere to extracellular matrix proteins, essential for colonization and the establishment of infections. Our results indicated that, except for the American isolates with a lower presence of fmtB and clfA genes, in the other seven countries these genes were widely present in the circulating isolates particularly in Brazilian and Tunisian ones.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, MRSA have been sporadically identified in bovine milk (Antoci, Pinzone, Nunnari, Stefani, & Cacopardo, 2013;Normanno et al, 2007;Pilla et al, 2012), while they have never been detected in surveys conducted on ovine, caprine or bubaline milk (Cremonesi et al, 2013;Morandi, Brasca, Andrighetto, Lombardi, & Lodi, 2010;Perillo et al, 2012;Spanu et al, 2013;Virdis et al, 2010). At a global level, only a few data are available on the presence of MRSA in dairy products.…”
Section: Phenotypic and Genomic Characterisation Of Methicillin Resismentioning
confidence: 95%
“…And more, as previously described [15], S. aureus isolates harbouring genes coding for clumping factor (clfA), a cell wall-associated protein (fmtB), and collagen-binding protein (cna) have a greater capability to adhere to extracellular matrix proteins, essential for colonization and the establishment of infections. Our results indicated that, except for the American isolates with a lower presence of fmtB and clfA genes, in the other seven countries these genes were widely present in the circulating isolates particularly in Brazilian and Tunisian ones.…”
Section: Discussionmentioning
confidence: 75%